2001
DOI: 10.1034/j.1399-302x.2001.160607.x
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation‐induced oral candidiasis in an experimental murine model

Abstract: The aim of this experiment was to establish a mouse model of irradiation-induced oral candidiasis and to explore the cellular populations and mechanisms by which the infection is cleared from the oral mucosa. BALB/c mice received irradiation to the head and neck equivalent to 800 Rad using a Cobalt 60 gamma source. Both irradiated and non-irradiated mice were infected orally with 1 x 10(8) Candida albicans yeasts. Compared with untreated controls, irradiated animals developed a more severe infection of longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
4
16
0
1
Order By: Relevance
“…Yeast strain 3630, routinely used in our laboratory, has been shown to establish reproducible infections in the brain, kidney and other tissues of inbred mice [25], and in the oral cavity [7]. The present experiments have confirmed these results, and further shown that yeast 3683, derived from an oral infection, was more efficient in infecting the oral mucosa, while retaining an ability to establish consistent systemic infections.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Yeast strain 3630, routinely used in our laboratory, has been shown to establish reproducible infections in the brain, kidney and other tissues of inbred mice [25], and in the oral cavity [7]. The present experiments have confirmed these results, and further shown that yeast 3683, derived from an oral infection, was more efficient in infecting the oral mucosa, while retaining an ability to establish consistent systemic infections.…”
Section: Discussionsupporting
confidence: 80%
“…Inbred mice differ in their susceptibility to systemic infection with the yeast [1e3], and some progress has been made in identifying the genetic basis of these differences [4e6]. In oral candidiasis, the increased tissue susceptibility of CBA/CaH mice relative to BALB/c has been confirmed [7], and DBA/2 mice show slightly different patterns of oral colonisation compared to BALB/c [8,9]. However, the extent to which host responses are related to global virulence properties of different Candida strains has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Rodents, especially mice, have been used to establish oropharyngeal candidiasis or more extensive fungal infections as a study model to test antifungal agents for treatment or for clinical monitoring of infection [29,[39][40][41][42][43][44]. SCID mice have been used by many investigators as a model to study mucosal candidiasis [40,45].…”
Section: Discussionmentioning
confidence: 99%
“…As such, MIF is involved in the immune response to infections caused by a variety of pathogens, including bacteria (Calandra 2003;Koebernick et al 2002;Wong et al 2009), parasites (Flores et al 2008;Martiney et al 2000;RodriguezSosa et al 2003;Sashinami et al 2006;Weiser et al 1991) and viruses (Arjona et al 2007;Assunç ão-Miranda et al 2010;Suzuki et al 2000). Data from experimental animal infection models have demonstrated involvement of MIF in fungal infections as well, including those caused by the respiratory fungus, Histoplasma capsulatum (Tewari and Von Behren 2000), Paracoccidioides brasiliensis (Defaveri et al 1992) and the opportunistic fungi, Candida albicans (Farah et al 2001;Nicolo et al 2006;Vorob ev et al 1983) and Cryptococcus neoformans (Graybill et al 1983). Involvement of MIF was noted in human candidiasis (Singh et al 1990) and sporotrichosis (Tanuma et al 2001).…”
Section: Introductionmentioning
confidence: 94%